Labour outcomes with defibulation at delivery in immigrant Somali and Sudanese women with type III female genital mutilation/cutting (Swiss Medical Weekly, 2020)
INTRODUCTION There is a scarcity of studies on labour outcomes with defibulation. This study assessed the outcomes of labour with defibulation at delivery in women with type III female genital mutilation/cutting (FGM/C) compared to labour without defibulation. METHODS We identified and reviewed the records of all Somali and Sudanese women who delivered at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, between January 2012 and December 2016. Labour outcomes of women with type III FGM/C who delivered vaginally with defibulation at delivery were compared to the outcomes of women without type III FGM/C who delivered vaginally without defibulation. Data extracted from the records included demographics, registration status, and labour outcomes. RESULTS During the study period, 1086 Somali and Sudanese women delivered at our institution, with 42% delivering by caesarean section. Among the 631 women with vaginal delivery, 27% had type III FGM/C and delivered with defibulation while 73% did not have type III FGM/C and delivered without defibulation. Demographic and clinical factors were similar between the two groups who delivered vaginally. The outcomes of labour with defibulation at delivery in women with type III FGM/C were not different from women without defibulation, except in regards to instrumental delivery and maternal blood loss. There were also no statistically significant differences between the two groups in neonatal outcomes. CONCLUSIONS Defibulation at delivery is an effective minor surgical procedure that should be in the armamentarium of the healthcare providers managing women with type III FGM/C.